(untitled) (Social Science Review, 2023)
Fisher Equation, asserted by Irving Fisher in his celebrated book ‘The Theory of Interest’, reveals that nominal interest rate adjusts with the inflation rate at the same rate in order to keep real interest rate constant. Using yearly time series data from Bangladesh for the period 1987 – 2020, this paper tested the validity of the Fisher effect considering the variables- Nominal Interest Rate (Advance Rate), Real Interest Rate and Inflation Rate. With a view to rationalizing the existence of structural break, Clemente - Montanes – Reyes (1998) unit root test was performed to identify the integration order of the variables of interest. After controlling structural break, Gregory- Hansen (1996) cointegration test applied for detecting the long run relationship by adopting ARDL framework. As the results revealed, Partial Fisher effect prevails for Bangladesh in short run. More specifically, keeping the real interest constant the impact of inflation rate on nominal interest rate is 0.16 percent with a lag effect in both ARDL model but parameters are stable only when we address structural break in the model. Thus, establishing that empirical identification of short run relationship among variables and existence of Fisher effect is subject to proper consideration of structural break. Social Science Review, Vol. 38(2), December 2021 Page 175-196